Laparoscopic pancreaticoduodenectomy in A-92-older Chinese patient for cancer of head of the pancreas: A Case report. Issue 3 (January 2017) - Zhou, Jiayu; Xin, Chang; Xia, Tao; Mou, Yiping; Xu, Xiaowu; Zhang, Renchao; Zhou, Yucheng; Jin, Weiwei; Lu, Chao
Abstract: Introduction: Laparoscopic pancreaticoduodenectomy (LPD) is one of the most complex gastrointestinal procedures performed in laparoscopic abdominal surgery. However, the concern for elderly undergoing LPD remains. To the best of our knowledge, there are no reports describing LPD for A-92-older patient. This study aimed to share the experience of a tertiary pancreatic center and confirm the safety, feasibility of LPD for the elderly. Method: The patient had complained of 6-months history of abdominal discomfort and progressive jaundice. Abdominal computed tomography CT/MR imaging revealed a 3 × 3 cm solid hypovascular mass in the head of the pancreas. LPD was successfully performed after multidisciplinary team (MDT). Operation time was 450 minutes, and blood loss was 120 mL. Histological examination of the resected specimen confirmed the diagnosis of pancreatic ductal adenocarcinoma (PDAC). Outcomes: The patient was discharged on POD13 following an uneventful postoperative period. She was followed up 4 months without any sign of recurrence. Conclusion: LPD can be performed safely in patients of any age who are fit for surgery in specialist centers.